Clinicopathological characteristics and treatment outcomes of fibrosing alopecia in a pattern distribution: A retrospective cohort study. (28th September 2021) - Jerjen, R.; Pinczewski, J.; Sinclair, R.; Bhoyrul, B.
Abstract: Background: Fibrosing alopecia in a pattern distribution (FAPD) is a primary cicatricial alopecia considered a subtype of lichen planopilaris (LPP). Objective: The clinical and histopathological features, and treatment response of 24 female patients with FAPD were evaluated. Methods: Demographic, clinical, histopathological and treatment data of patients with FAPD were retrospectively collected. Results: Twenty‐four women were included (mean age 60.7 years). The mean Lichen Planopilaris Activity Index score was 1.50, and the median Sinclair grade was 3. Twelve patients had diffuse alopecia in the centroparietal region, four had frontal accentuation and eight had vertex accentuation of hair loss. Eight had associated loss of facial hair. Predominant trichoscopic features included hair shaft diameter variability (100%), perifollicular erythema and/or scaling (95%) and loss of follicular ostia (95%). Histopathological examination revealed features of scarring alopecia with interface changes in follicular epithelia mainly targeting terminal and intermediate hairs, and less frequently, vellus hairs. Treatment with hair growth‐promoting, anti‐inflammatory and anti‐androgen agents arrested disease progression in 14 patients and resulted in hair regrowth in two patients. Six patients had progression of their hair loss in spite of treatment. Limitations: Referral bias to a specialist hair clinic, retrospective design and small sample size. Conclusions: We present clinicopathological features of FAPD which can aid in the diagnosis of this insidious scarring alopecia. Our findings suggest a more favourable outcome if treatment is initiated in early stages of the disease.